ANALISIS TERMINOLOGI PERPECAHAN DARI PERSPEKTIF HADIS: TERMINOLOGY ANALYSIS OF DISUNITY FROM THE PERSPECTIVE OF HADITH - Abu Bakar , Ahmad Izzuddin (International Prophetic Conference (SWAN) FPQS USIM, 2022)
Disunity is an evergreen issue that reverberates among the Muslim community, especially when certain events such as the General Election and the Israeli-Palestinian conflict occur. This can be seen and felt in social media and public conversations. However, there is ambiguity on the true meaning of the disunity prohibited by religion. If someone accuses the person of disuniting the people, he will deny his actions for various reasons. Hence, this study will analyze the things that are categorized as disunity according to the Prophetic Hadith. The method used is a qualitative method, specifically content analysis. The hadiths that contain the word disunity will be analyzed based on the authoritative commentaries books. The findings summarize four things that are considered as an act of disuniting society and the country. First: differences in religious beliefs or propositions; second: not guided by the guidance and evidence from the Quran and Hadith in faith and practice; third: a difference of opinion that leads to contention and enmity and fourth: fighting the government using weapons or rebelling or as named in jurisprudence as khuruj.